Investigating geospatial models of the diffusion of morphosyntactic innovations: The Welsh strong second-person singular pronoun chdi. Issue 1 (10th August 2017) - Willis, David
Abstract : Morphosyntactic dialect variation, once a neglected area of dialect research, has recently witnessed a large growth in interest. Various methods from geospatial data analysis have been applied to morphosyntactic data. To date, the focus has largely been on analyzing the distribution of stable patterns of variation. This article extends this work to examine patterns of ongoing change. It uses a body of data from the Syntactic Atlas of Welsh Dialects and the Siarad Corpus of spoken Welsh to examine the innovation and diffusion of a new second-person singular pronoun, chdi, testing the usefulness of Geographically Weighted Regression (GWR) as a method for identifying and modeling patterns of ongoing syntactic change. It is shown that GWR provides plausible models of the diachronic development of changes that are still in progress. Furthermore, it allows us to test whether rates of change are constant across geographical space, allowing us to test whether the Constant Rate Hypothesis (that diffusion of change proceeds at the same rate in different environments) holds between dialects.